2018
DOI: 10.11114/jets.v6i10.3538
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis on Values Education Programme for Preschool Students

Abstract: In recent years, there is a big debate among researchers, teachers and decision makers about what to include in early childhood values education in preschools in Turkey. The aim of the current study is to make a need analysis for values education programme for preschoolers. This study was conducted with 200 preschool teachers in one of urban cities of Turkey –Kahramanmaraş- during 2016-2017 Spring semester. A values checklist is created for the current study by making use of Turkish Ministry of Education’s ‘Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Studies of needs analysis have been undertaken over the last three decades (Widodo, 2016) and a number of contemporary researches on this issue have mushroomed in many different countries, such as Greece (Chostelidou, 2010;Tzotzou, 2014), Iran (Aliakbari & Boghayeri, 2014;Atai & Shoja, 2011;Boroujeni & Fard, 2013;Eslami, 2010;Mohammadi & Mousavi, 2013;Moiinvaziri, 2014), Spain (Benavent & Sánchez-Reyes, 2015;Peters & Fernández, 2013), Sudan (Elsaid Mohammed & Nur, 2018), USA (Bosher & Smalkoski, 2002;Serafini, Lake, & Long, 2015), Japan (Cowling, 2007), China (Guiyu & Yang, 2016;Li, 2014;Wu, 2012;Zhu & Liu, 2014), Turkey (Akyel & Ozek, 2010;Kayiran & Bağçeci, 2018), KSA (Abdalla & Mohammed, 2016;Al-Qahtani, 2015;Alsamadani, 2017;Fadel & Rajab, 2017), Taiwan (Chen, Chang, & Chang, 2016;Lu, 2018), Thailand (Bosuwon & Woodrow, 2009;Prachanant, 2012), and Indonesia (Nimasari, 2018;Poedjiastutie & Oliver, 2017;Sabarun, 2019;Salam, 2017). Those literatures reflect the centrality and the inevitable role of need analysis in establishing an ESP course.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of needs analysis have been undertaken over the last three decades (Widodo, 2016) and a number of contemporary researches on this issue have mushroomed in many different countries, such as Greece (Chostelidou, 2010;Tzotzou, 2014), Iran (Aliakbari & Boghayeri, 2014;Atai & Shoja, 2011;Boroujeni & Fard, 2013;Eslami, 2010;Mohammadi & Mousavi, 2013;Moiinvaziri, 2014), Spain (Benavent & Sánchez-Reyes, 2015;Peters & Fernández, 2013), Sudan (Elsaid Mohammed & Nur, 2018), USA (Bosher & Smalkoski, 2002;Serafini, Lake, & Long, 2015), Japan (Cowling, 2007), China (Guiyu & Yang, 2016;Li, 2014;Wu, 2012;Zhu & Liu, 2014), Turkey (Akyel & Ozek, 2010;Kayiran & Bağçeci, 2018), KSA (Abdalla & Mohammed, 2016;Al-Qahtani, 2015;Alsamadani, 2017;Fadel & Rajab, 2017), Taiwan (Chen, Chang, & Chang, 2016;Lu, 2018), Thailand (Bosuwon & Woodrow, 2009;Prachanant, 2012), and Indonesia (Nimasari, 2018;Poedjiastutie & Oliver, 2017;Sabarun, 2019;Salam, 2017). Those literatures reflect the centrality and the inevitable role of need analysis in establishing an ESP course.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a need analysis was carried out in order to determine whether preschool teachers need a values education program and what they need if they do. Although values education is an increasingly important topic in Türkiye, there is no values education program in preschool education (Kayıran & Bağçeci, 2018). Creating an effective training program is only possible by determining the needs in the required fields.…”
Section: Collection Of the Datamentioning
confidence: 99%
“…Ergin and Karataş (2014) conducted a study with teachers and determined that family was one of the determining factors in values education and that the values taught by school and family conflicted. Kayıran and Bağçeci (2018) found that the most important values according to preschool teachers were honesty, patriotism, responsibility, justice, and respect for older adults and the environment. In Şahin (2019), preservice teachers emphasized that the primary goal of values education should be to turn students into good citizens.…”
Section: Introductionmentioning
confidence: 99%
“…In Ulusoy (2021), history teachers (n=30) stated that the history curriculum should include alternative activity examples instead of just giving definitions and information, that materials should be provided free of charge by schools, that activities should be carried out to prevent peer bullying, and that there should be more activities and operations for women's rights. Most studies on values and values education focus on teachers and preservice teachers (Akan, 2021;Bayırlı, Doruk & Tüfekçi 2020;Çalışkan, Yıldırım, & Demirhan, 2021;Duban & Aydoğdu, 2016;Durdukoca Firat, 2019;Ekşi & Kaya, 2021;Kamer & Şahin, 2021;Katmış & Balcı, 2017;Kayıran & Bağçeci, 2018, Okumuş, 2021Oğuz, 2012;Yazar, 2012;Yildiz-Göğebakan & Pala, 2021). However, there is limited research on academics.…”
Section: Introductionmentioning
confidence: 99%